Gut microbiome of migratory shorebirds: Current status and future perspectives. Issue 9 (3rd April 2021) - Zhang, Zheng; Yang, Zhisong; Zhu, Lifeng
Abstract: Migratory shorebirds have many unique life history characteristics, such as long‐distance travel between breeding sites, stopover sites, and wintering sites. The physiological challenges for migrant energy requirement and immunity may affect their gut microbiome community. Here, we reviewed the specific features (e.g., relatively high proportion of Corynebacterium and Fusobacterium ) in the gut microbiome of 18 migratory shorebirds, and the factors (e.g., diet, migration, environment, and phylogeny) affecting the gut microbiome. We discussed possible future studies of the gut microbiome in migratory shorebirds, including the composition and function of the spatial‐temporal gut microbiome, and the potential contributions made by the gut microbiome to energy requirement during migration. Abstract : We synthesised published 16S rRNA gene data in the migratory shorebirds (Cho & Lee, 2020; Grond et al., 2019, 2020; Risely et al., 2017, 2018), and found the predominant phyla of these 13 shorebird species include Firmicutes, Bacteroidetes, Proteobacteria, Fusobacteria, and Actinobacteria.